Development of a double-MRT pseudopotential model for tridimensional boiling simulation - Fogliatto, Ezequiel Oscar; Clausse, Alejandro; Teruel, Federico Eduardo (Elsevier France-Editions Scientifiques Medicales Elsevier, 2022)
Fil: Fogliatto, Ezequiel Oscar. Comisión Nacional de Energía Atómica; Argentina